1996
DOI: 10.1046/j.1365-2958.1996.357881.x
|View full text |Cite
|
Sign up to set email alerts
|

The local repressor AcrR plays a modulating role in the regulation of acrAB genes of Escherichia coli by global stress signals

Abstract: Genes acrAB encode a multidrug efflux pump in Escherichia coli. We have previously reported that transcription of acrAB is increased under general stress conditions (i.e. 4% ethanol, 0.5 M NaCl, and the stationary phase in Luria-Bertani medium). In this study, lacZ transcriptional fusions and an in vitro gel mobility shift assay have been utilized to study the mechanisms governing the regulation of acrAB. We found that a closely linked gene, acrR, encoded a repressor of acrAB. Nevertheless, the general stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
293
1
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(312 citation statements)
references
References 39 publications
12
293
1
5
Order By: Relevance
“…Recently, Nakajima et al (20) showed that overexpression of RobA in E. coli produced multiple resistance to antibiotics and heavy metals, including Ag. Since RobA activates the transcription of acrAB efflux pump genes (13), it may also increase the expression of a similar efflux system that is capable of pumping out heavy metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nakajima et al (20) showed that overexpression of RobA in E. coli produced multiple resistance to antibiotics and heavy metals, including Ag. Since RobA activates the transcription of acrAB efflux pump genes (13), it may also increase the expression of a similar efflux system that is capable of pumping out heavy metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated the induction pathway of acrAB in Salmonella in response to paraquat. In addition to RamA, AcrAB is regulated by three activators, MarA, SoxS and Rob, Salmonella AcrAB regulation by indole and paraquat and one repressor, AcrR (Ma et al, 1996;Randall & Woodward, 2002;Rosenberg et al, 2003). We used deletion mutants of these regulators to investigate whether they were required for acrAB induction in response to paraquat.…”
Section: Paraquat Induces Acrab Via the Soxs Regulator And Not Via Thmentioning
confidence: 99%
“…The acrAB regulation mechanism must be examined to understand the physiological role of AcrAB. In Escherichia coli, AcrAB is regulated by three activators, MarA, SoxS and Rob, and one repressor, AcrR (Ma et al, 1996;Randall & Woodward, 2002;Rosenberg et al, 2003). In Salmonella, RamA is involved in inducing acrAB in addition to the (Bailey et al,2008 ;Schneiders et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins in this family bind in the vicinity of the promoters of their respective target genes (8,14). To examine whether MphR(A) is the repressor protein that controls expression of mph(A), we constructed an mphR(A) expression system and purified MphR(A).…”
Section: Specific Binding Of Mphr(a) To the Promoter Region Of Mph(a)mentioning
confidence: 99%